SVCT2 vitamin C transporter expression in progenitor cells of the postnatal neurogenic niche - Pastor, Patricia; Cisternas, Pedro; Salazar, Katterine; Silva-Alvarez, Carmen; Oyarce, Karina; Jara, Nery; Espinoza, Francisca; Martínez, Agustin; Nualart, Francisco J. (Frontiers in Cellular Neuroscience, 2013)
Known as a critical antioxidant, recent studies suggest that vitamin C plays an important role in stem cell generation, proliferation and differentiation. Vitamin C also enhances neural differentiation during cerebral development, a function that has not been studied in brain precursor cells. We observed that the rat neurogenic niche is structurally organized at day 15 of postnatal development, and proliferation and neural differentiation increase at day 21. In the human brain, a similar subventricular niche was observed at one-month of postnatal development. Using immunohistochemistry, sodium-vitamin C cotransporter 2 (SVCT2) expression was detected in the subventricular zone and rostral migratory stream. Low co-distribution of SVCT2 and βIII-tubulin in neuroblasts or type-A cells was detected, and minimal co-localization of SVCT2 and GFAP in type-B or precursor cells was observed. Similar results were obtained in the human neurogenic niche. However, BrdU-positive cells also expressed SVCT2, suggesting a role of vitamin C in neural progenitor proliferation. Primary neurospheres prepared from rat brain and the P19 teratocarcinoma cell line, which forms neurospheres in vitro, were used to analyze the effect of vitamin C in neural stem cells. Both cell types expressed functional SVCT2 in vitro, and ascorbic acid induced their neural differentiation, increased βIII-tubulin and SVCT2 expression, and amplified vitamin C uptake.